(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
The prime objective was development and pharmacokinetic characterization of pulsatile drug delivery systems (PDDS) to gain chronomodulated delivery of Esomeprazole (EMP) suitable for combating nocturnal acid breakthrough (NAB). Analytical method by HPLC was developed for the quantification of EMP from the biological samples. In vivo bioavailability testing was accomplished on Sprague–Dawley rats for the developed PDDS formulation. In-vitro in-vivo correlation (IVIVC) was carried out by deconvolution method. The bioanalytical approach that was developed exhibited linearity within the range of 100-2000ng/mL with correlation coefficient of 0.999. The results of other method validation parameters were found satisfactory. The in-vivo studies on the PDDS specified that the EMP was released as two pulses at the desired times. The AUC and MRT from the PDDS were found to be increased by 3.02 times and 2.2 times respectively in comparison with the marketed formulation. IVIVC revealed that considerably good correlation was observed. The established bioanalytical approach proved to be appropriate for quantifying EMP in biological samples. The developed PDDS formulation of EMP was effective to combat the NAB condition.